2018
DOI: 10.1214/17-aoas1105
|View full text |Cite
|
Sign up to set email alerts
|

Reducing storage of global wind ensembles with stochastic generators

Abstract: Wind has the potential to make a significant contribution to future energy resources. Locating the sources of this renewable energy on a global scale is however extremely challenging, given the difficulty to store very large data sets generated by modern computer models. We propose a statistical model that aims at reproducing the data-generating mechanism of an ensemble of runs via a Stochastic Generator (SG) of global annual wind data. We introduce an evolutionary spectrum approach with spatially varying para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…where H r (c, L m , t k ) is the spectral process assumed to be independent across wavenumbers, c. Hence, for the storage and computation of f (c), model (4) requires O(N ) entries and O(N logN ) operations, respectively, as opposed to the covariance function, which requires O(N 2 ) entries and O(N 3 ) operations, respectively. We can also generalize (4) to allow for changing behavior across domains such as land and ocean (Castruccio and Guinness, 2017) or altitude (Jeong et al, 2018). Besides diminishing the storage and computational burdens, this approach allows the inference to be performed in parallel across m, i.e., across latitude, following Principle 2.…”
Section: Spectral Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where H r (c, L m , t k ) is the spectral process assumed to be independent across wavenumbers, c. Hence, for the storage and computation of f (c), model (4) requires O(N ) entries and O(N logN ) operations, respectively, as opposed to the covariance function, which requires O(N 2 ) entries and O(N 3 ) operations, respectively. We can also generalize (4) to allow for changing behavior across domains such as land and ocean (Castruccio and Guinness, 2017) or altitude (Jeong et al, 2018). Besides diminishing the storage and computational burdens, this approach allows the inference to be performed in parallel across m, i.e., across latitude, following Principle 2.…”
Section: Spectral Methodsmentioning
confidence: 99%
“…Here, we show only the temporal dependence; we defer the longitudinal and latitudinal step to the next section. We apply Principle 2 to model (3) below; the diagnostics can be found for annual wind speed in Jeong et al (2018) and for temperature in Castruccio and Genton (2016). If the vector of all values of r at time t k is denoted by r (t k ), then…”
Section: Stepwise Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…3(a) for a snapshot). A similar app, called 'global surface wind' displays the annual winds between 1920 and 2100 across the globe according to a climate model and another statistical model (full details on the model are provided by Jeong et al (2018)). This app uses a similar visualization scheme to that in the temperature case, but it lacks the three-dimensional component as the model focuses on surface wind speed.…”
Section: Portable Virtual Reality: Smartphone Applicationsmentioning
confidence: 99%
“…In particular, the multi-step spectrum model was designed to consider nonstationary covariance models across longitudes and to allow analysis of very large datasets by evaluating the likelihood with parallel and distributed computing. Castruccio and Guinness (2017) and Jeong et al (2018) showed how these models can be coupled with a land/ocean indicator and mountain ranges in the evolutionary spectrum. Since data from orbiting satellites have a particular observational location structure, the implementation of the above spectrum procedure on a non-gridded structure may be problematic.…”
Section: Nonstationary Covariance Models On the Spherementioning
confidence: 99%